Relationship of Dye Adsorption Onto Biomass Activated Carbon Mixed Matrix Ultrafiltration: A Mass Transfer Model Study - Khairul Anwar, Mohamad Said; Shaiza, Asif; Siti Zahara May, Abdullah; Ibrahim, Yakub; Harunal Rejan, Ramji; Md Rezaur, Rahman (Wiley-VCH GmbH, 2026)
The purpose of this study was to investigate the adsorption of dye molecules from water resources, with a particular emphasis on the use of activated carbon as an adsorbent in polymer membranes to purify low-quality waters to produce clean water. Polyvinylidene fluoride (PVDF) membranes’ removal efficiency was substantially enhanced by the initial concentration of 10 ppm methylene blue (MB). 1.07 ppm of MB was present in the pristine membrane, resulting in a removal efficiency of 89.29%. The removal efficacy was observed to increase to 96.34% when PVDF membranes were incorporated with biomass-activated carbon (BAC). Removal efficiency is substantially determined by the initial concentration of the adsorbate solution. The initial concentration of 0.5 mg/L resulted in the removal of nearly 100% of MB. The modification of the mass transfer model proposed has the broadest applicability in determining the resistance of mass transfer for the adsorption process. In relation to the adsorption of dye onto biomass-activated carbon, the influence of surface area occupation is driven by film mass transfer. The importance of the role of surface area occupation in modulating the resistance of mass transfer in the adsorption is emphasized by the fact that the film mass transfer increased as the driving force of mass transfer (C-C*) increased.